2019
DOI: 10.1007/s00417-019-04242-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses after vitrectomy with vitreous substitutes in a rabbit model

Abstract: Purpose To investigate the inflammatory response of current and future potential vitreous substitutes in an experimental in vivo vitrectomy model. Methods Twenty-five gauge pars plana vitrectomy was performed in the right eye of 60 pigmented rabbits, with subsequent injection of 0.5-1.0 ml of Healaflow® (cross-linked hyaluronic acid, n = 12), Bio-Alcamid® (polyalkylimide, n = 8), silicone oil (n = 12), or balanced saline solution (BSS, n = 28). Postoperative clinical evaluation was performed; and the rabbits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…In previous studies using HF in normal eyes, we found no signs of excessive inflammation. 13,14 The fact that 2/8 HF filled eyes in the present study developed this complication after repeat surgery indicates that the tamponading gel may induce different tissue reactions within a pathological environment. This is also highlighted by the one repeat surgery HF eye in which severe retinal degeneration in an attached area was noted.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In previous studies using HF in normal eyes, we found no signs of excessive inflammation. 13,14 The fact that 2/8 HF filled eyes in the present study developed this complication after repeat surgery indicates that the tamponading gel may induce different tissue reactions within a pathological environment. This is also highlighted by the one repeat surgery HF eye in which severe retinal degeneration in an attached area was noted.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously described models for studying various vitreous substitutes in vitro and in vivo. [10][11][12][13][14] A new potential vitreous substitutecross-linked hyaluronic acid hydrogel, Healaflow® (HF) -in these experiments has been found to exhibit excellent biocompatibility in vitro as well as in normal rabbit eyes in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A big discrepancy in the number of publications on hydrogel vitreous substitutes and vitreous humor in the years 1995-2000 (9 publications and 0 publications, respectively) should be noted, considering the approval of silicone oil for use as a vitreous substitute by the Food and Drug Administration (FDA) in 1994. 58 Synthetic 33,34,59-91 and semisynthetic [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] hydrogels have been more common materials for experimental vitreous substitutes in recent years, while natural hydrogels 37,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123] were much more prevalent in the early years ( Figure 3B). The foldable capsular vitreous body (FCVB) is a different polymeric design for a vitreous substitute that is currently undergoing clinical trials in China.…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 99%
“…Moreover, a pressure-induced retinal atrophy was observed due to the lack-based fixation process. However, the immunohistological results proved that there was no significant increase in CD45-positive cells, meaning no immigration of inflammatory cells into the retina as immune reaction [28]. Therefore, we can assume that further improvements in the design of such structures are necessary, but that they are fundamentally suitable for stimulating the retina and enable new ways of transmitting signals and energy into a retinal implant.…”
Section: Discussionmentioning
confidence: 99%